2005
DOI: 10.1016/j.ejcts.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of valve replacement with modern prostheses in young adults

Abstract: Late outcomes of modern prosthetic valves in young adults remain suboptimal. Bioprostheses deserve consideration in the aortic position, as mechanical valves are associated with lower physical capacity, a higher prevalence of disability, and poorer disease perception. Early surgical referral and atrial fibrillation surgery may improve survival after MVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
73
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 19 publications
11
73
0
4
Order By: Relevance
“…At 2 years, there were no significant differences in mortality from any cause between the TAVR group (33.9%; 95% CI, 28.9 to 39.0) and the surgery group (35.0%; 95% CI, 29.8 to 40.2; P = 0.78) ( Table 1). Cardiovascular mortality at 2 years was also similar in the TAVR and surgery groups (21.4% [95% CI, 16.8 to 26.0] and 20.5% [95% CI, 15.8 to 25.3], respectively; P = 0.80). Similarly, in the as-treated analysis, the TAVR and surgery groups did not differ significantly with respect to all-cause mortality (33.9% and 32.7%, respectively; P = 0.75) or cardiovascular mortality (20.8% and 18.5%, respectively; P = 0.50) ( Table 2 in the Supplementary Appendix).…”
Section: Mortality and Strokementioning
confidence: 67%
See 1 more Smart Citation
“…At 2 years, there were no significant differences in mortality from any cause between the TAVR group (33.9%; 95% CI, 28.9 to 39.0) and the surgery group (35.0%; 95% CI, 29.8 to 40.2; P = 0.78) ( Table 1). Cardiovascular mortality at 2 years was also similar in the TAVR and surgery groups (21.4% [95% CI, 16.8 to 26.0] and 20.5% [95% CI, 15.8 to 25.3], respectively; P = 0.80). Similarly, in the as-treated analysis, the TAVR and surgery groups did not differ significantly with respect to all-cause mortality (33.9% and 32.7%, respectively; P = 0.75) or cardiovascular mortality (20.8% and 18.5%, respectively; P = 0.50) ( Table 2 in the Supplementary Appendix).…”
Section: Mortality and Strokementioning
confidence: 67%
“…Nevertheless, structural valve deterioration is well known with surgical bioprostheses, and definitive assessments of valve durability will require much longer follow-up. [24][25][26] A design limitation of transcatheter aortic valves has been paravalvular regurgitation, which results from incomplete circumferential apposition of the prosthesis with the annulus. Several reports have indicated a relation between paravalvular regurgitation and mortality, but the certainty of these findings has been limited by the lack of standardization of methods to assess aortic regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Younger patients also may opt for a bioprosthesis at the time of valve surgery to avoid long-term oral anticoagulation, which is associated with hemorrhage and worse disease perception. 9 Recent North American data indicate that bioprostheses are increasingly used in patients less than 65 years of age who undergo aortic valve replacement (AVR) or mitral valve replacement (MVR). 10 -12 We and others have shown that patients between 18 and 60 years of age who select a bioprosthesis at the time of initial heart valve surgery have an increased reoperation risk but experience no long-term survival detriment compared with patients who select a mechanical valve.…”
mentioning
confidence: 99%
“…La implementación de la Operación de Ross en nuestro medio se puede hacer con resultados operatorios satisfactorios y comparables a los re portados para el reemplazo valvular aórtico con prótesis convencionales 11 . El número de pacientes presentados en esta serie nos permite analizar los problemas de la curva de aprendizaje.…”
Section: Discussionunclassified